GESTATIONAL HYPERTENSION AND HEALTH INIQUITY: A SYSTEMATIC REVIEW OF NUTRITIONAL MANAGEMENT IN THE BLACK POPULATION (Editora Impacto Científico, 2025)
In Brazil, gestational hypertension (GH) reveals a serious health inequity, with maternal mortality being disproportionately higher among the Black population. This disparity is a direct reflection of social determinants and structural racism, which persist despite advances in public policy. Concurrently, poor nutrition and inadequate nutritional status are factors directly linked to negative outcomes. Despite the urgency of this issue, science lacks studies focused on practical interventions, which limits the development of specific and equitable nutritional management protocols. This scenario reinforces the need for research that analyzes how nutritional management is implemented for this population, aiming to generate knowledge to improve protocols. The ultimate goal is to strengthen the role of the dietitian as a change agent, capable of promoting health equity.DOI: https://doi.org/10.56238/edimpacto2025.091-010